ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT MENGAJUKAN PEMBIAYAAN KPR DI BTN SYARIAH (Studi Pada Kasus di Kecamatan Pamijahan Kabupaten Bogor, Jawa Barat) - Hesti Safitri; Tubagus Rifqy Thantawi; Ermi Suryani (SAHID BANKING JOURNAL, 2021)
Abstract Owning a home is a basic human need that must be met. This is where Islamic banks provide. As a result, Islamic banks provide a variety of housing finance (KPR) in accordance with Islamic principles, which can be selected according to the needs of the community. By offering different prices, strategic housing with industrial and economic centers as well as promotional activities can attract public interest in sharia financing through the sharia banking system. the research aims to find out whether the product, price, location, promotion, religious belief, knowledge, administrative costs, service quality, and economic capacity are positive for the benefit of the community applying for Islamic mortgage financing. This type of research is quantitative research conducted using data collection methods using raw data obtained through a questionnaire survey. The sample size is 100. The hypothesis testing method is multiple linear regression, t-test, f-test, and the coefficient of determination (adjusted R-squared). The results showed that product tcount was 2.506 > t table 1.98447, sig value was 0.014 <0.05, price tcount was 3.119 > t table 1.98447, sig value was 0.002 <0.05, and promotion had a tcount value 2.167 > t table 1.98447, sig value 0.033 <0.05, tcount service quality 2.012 > ttable 1.98447, sig value 0.047 <0.05, tcount economic capacity 3.69 > ttable 1.98447, t sig value is 0.000 <0, 05, so it can be concluded that the variables of product, price, promotion, service quality and economic capacity will affect people's interest in applying for Sharia KPR. Locality, religion, knowledge and administrative costs do not affect people's interest in applying for sharia mortgage funds. The variables of product, price, location, promotion, religious belief, knowledge, administrative costs, quality of service, and economic capacity all influence societal interests at the same time. The sig value of Fcount>Ftable (23.318>2.04) is 0.000 <0.05. Adjusted R-squared value = 0.670 or 0.67%, and the remaining 3.3% is influenced by other factors.